2019
DOI: 10.1097/tp.0000000000002799
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects of Rabbit Anti-thymocyte Globulin Preparations on Primary Human Thymic Epithelial Cells

Abstract: Background. Graft-versus-host disease (GvHD) presents a major cause for morbidity and mortality after allogeneic hematopoietic stem cell transplantation. Rabbit-derived antithymocyte globulin (rATG) treatment reduces the incidence of GvHD after allogeneic hematopoietic stem cell transplantation. However, delayed immune reconstitution following rATG treatment, partly caused by hampered thymic function, is being discussed. The present study aims at elucidating possible cytotoxic effects of 2 commonly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In contrast, in the high ATG/lymphocyte ratio group, the thymus size was significantly smaller in all age groups. Previously published studies have demonstrated that rabbit-derived ATG preparations exert a dose-dependent cytotoxic effect on primary human thymic stromal cells, particularly thymic epithelial cells [ 46 ]. Comparing RTE production at one year from HSCT in ATG-exposed and non-exposed patients, we found a significant delay in the ATG-exposed group.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the high ATG/lymphocyte ratio group, the thymus size was significantly smaller in all age groups. Previously published studies have demonstrated that rabbit-derived ATG preparations exert a dose-dependent cytotoxic effect on primary human thymic stromal cells, particularly thymic epithelial cells [ 46 ]. Comparing RTE production at one year from HSCT in ATG-exposed and non-exposed patients, we found a significant delay in the ATG-exposed group.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, both CD31 + RTE counts and sjTREC levels decreased to the nadir at the end of chemotherapy and recovered within one year of follow-up ( 74 ). Similarly, the combination of total body irradiation with cyclophosphamide chemotherapy damaged the thymocytes and distorted T cell repertoire ( 75 ).Certain immunomodulatory medications such as rabbit anti-thymocyte globulin (rATG) also decrease TECs expression and secretion of interleukins with increased thymocytes apoptosis and delayed immune regeneration ( 76 ).…”
Section: Thymic Injury: Factors and Agentsmentioning
confidence: 99%
“…By contrast, concordant data exist to state that thymic output do not increase in non-ATG treated patients and decrease in those having received ATG (127,128). In vitro, ATG binds to TEC and exerts a complement-independent, dose-dependent cytotoxicity (129). Nevertheless, Preville et al (130) suggested that ATG could not enter into the thymus.…”
Section: Kidney Transplantationmentioning
confidence: 99%